FORMULASI DAN UJI AKTIVITAS SEDIAAN KRIM DARI EKSTRAK DAUN JAMBU BIJI (PSIDIUM GUAJAVA L.) SEBAGAI PENGOBATAN LUKA DIABETES - Hieronima Vivin Triana Sinaga (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Introduction: Bacterial infections, especially Staphylococcus aureus, often accompany diabetic wounds, which are chronic consequences of diabetes mellitus. These infections slow the healing process and raise the risk of further problems. As a safe and useful supportive therapy, topical formulations based on natural ingredients must be developed. Objective: To formulate a cream preparation with an ethanolic extract of guava leaves (Psidium guajava L.) and assess its physical characteristics and antimicrobial efficacy against Staphylococcus aureus. Methods: 96% ethanol was used to macerate the extract, which was then screened for bioactive compounds utilizing phytochemicals. An oil-in-water (O/W) basis was used to create the cream in three extract concentrations (10%, 20%, and 30%). Organoleptic characteristics, homogeneity, pH, and spreadability tests were among the physical assessments. Antibacterial activity was assessed using the disc diffusion method. Results: Phytochemical screening confirmed the presence of flavonoids, tannins, saponins, and steroids. All cream formulations met the physical quality requirements for topical application. Both the extract and cream exhibited strong antibacterial activity against Staphylococcus aureus. Conclusion: The guava leaf ethanolic extract cream shows potential as a supportive topical therapy for controlling infections in diabetic wounds; however, further studies are required to evaluate long-term stability, broader antibacterial spectrum, and in vivo effectiveness.